2019
DOI: 10.3389/fpls.2019.00244
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Functionality and Fertility Are Reduced by Heat and Drought Co-stress in Wheat

Abstract: As a consequence of climate change, unpredictable extremely hot and dry periods are becoming more frequent during the early stages of reproductive development in wheat (Triticum aestivum L.). Pollen sterility has long been known as a major determinant of fertility loss under high temperature and water scarcity, but it will be demonstrated here that this is not the exclusive cause and that damage to female reproductive organs also contributes to losses of fertility and production. Changes in the phenology, morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 76 publications
3
51
0
Order By: Relevance
“…Grain number was mostly increased by the same allele as grain weight in both GWAS and NILs, indicating an important factor under post-anthesis drought and heat stress. Grain number is known to be affected by pre-anthesis stress (Fabian et al, 2019) but has also been found to be decreased by postanthesis stress (Prasad et al, 2011;Qaseem et al, 2018). Grain number, in our experiments, accounted for only well-filled grains Alleles for Drought and Heat Tolerance in Wheat (i.e., grains of size > 2.0 mm).…”
Section: Important Drought and Heat Tolerance Traitssupporting
confidence: 41%
“…Grain number was mostly increased by the same allele as grain weight in both GWAS and NILs, indicating an important factor under post-anthesis drought and heat stress. Grain number is known to be affected by pre-anthesis stress (Fabian et al, 2019) but has also been found to be decreased by postanthesis stress (Prasad et al, 2011;Qaseem et al, 2018). Grain number, in our experiments, accounted for only well-filled grains Alleles for Drought and Heat Tolerance in Wheat (i.e., grains of size > 2.0 mm).…”
Section: Important Drought and Heat Tolerance Traitssupporting
confidence: 41%
“…The main method of pollination in these domesticated vines is self-fertilization. However, in an inflorescence, the percentage of ovaries yielding fruit is strongly variable, and is affected by different factors including environmental changes such as light, temperature, and water stress (Lecourieux et al , 2017; Fábián et al ., 2019), but also vineyard management and grape variety features (Dry et al , 2010). Indeed, low fruit set can limit crop yield, resulting in losses to grape and wine production.…”
Section: Discussionmentioning
confidence: 99%
“…Water stress and high temperature are the exclusive cause that damages the female reproductive organs which leads to losses of fertility and production. Therefore, pollen sterility is not the major determinant of fertility loss under high temperature and water scarcity (Fábián et al, 2019). In wheat, higher temperature and water stress collectively reduced 66% to 93% rate of photosynthetic compared with non-stress conditions.…”
Section: Introductionmentioning
confidence: 99%